2018
DOI: 10.1111/pcn.12651
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of Lewy body disease in patients with late‐onset psychiatric disorders using clinical history of rapid eye movement sleep behavior disorder and [123I]‐metaiodobenzylguanidine cardiac scintigraphy

Abstract: The severity of %RWA was highly correlated with the value of cardiac [ I]-MIBG uptake, but not with specific binding ratio on DAT scan. Clinical history of RBD and cardiac [ I]-MIBG scintigraphy are helpful for an early differential diagnosis of LBD from late-onset psychiatric disorders, even before parkinsonism or dementia appears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Reduced meta-iodobenzylguanidine (MIBG) uptake is an indicative biomarker for DLB 2 and has also been reported to occur in a small series of patients with late-onset psychiatric disorder and PSG-confirmed RBD, 32 reinforcing its association with underlying α-synucleinopathy. Of 2 patients with amnestic MCI with low MIBG uptake, one developed DLB after 2 years; the other had no clinical follow-up reported.…”
Section: Polysomnographic Confirmation Of Rem Sleep Without Atoniamentioning
confidence: 90%
See 1 more Smart Citation
“…Reduced meta-iodobenzylguanidine (MIBG) uptake is an indicative biomarker for DLB 2 and has also been reported to occur in a small series of patients with late-onset psychiatric disorder and PSG-confirmed RBD, 32 reinforcing its association with underlying α-synucleinopathy. Of 2 patients with amnestic MCI with low MIBG uptake, one developed DLB after 2 years; the other had no clinical follow-up reported.…”
Section: Polysomnographic Confirmation Of Rem Sleep Without Atoniamentioning
confidence: 90%
“…53 Further studies need to confirm these findings and to determine the value of other DLB biomarkers in psychiatric-onset cases. 32,52,56 In summary, it is not yet clear how to identify patients with prominent late-onset psychiatric symptoms who may have underlying LB disease and subsequently progress to DLB. It is premature to try to construct formal criteria for psychiatriconset DLB, but clinicians in mental health and other settings need to be aware that this possibility exists, not least because of the risk of severe antipsychotic sensitivity reactions with increased morbidity and mortality.…”
Section: Identification Of Delirium-onset Dlbmentioning
confidence: 99%
“…Also, patient #1 presented two core clinical features (namely fluctuating cognition and parkinsonism), five supportive clinical features (namely sensitivity to antipsychotic agents, postural instability, repeated falls, autonomic dysfunction, and depression), one indicative biomarker (reduced dopamine transporter uptake in basal ganglia by SPECT), and two supportive biomarkers (relative preservation of medial temporal lobe structures on MRI scan, generalized low uptake on PET metabolism scan with reduced occipital activity) (9). Others DLB prodromal symptoms include dysautonomia, olfactory dysfunction, rapid eye movement sleep behavior disorder (RBD) (11). The patient suffered from resistant constipation and repeated falls when he was admitted, but no other DLB usual prodromes were found in his history.…”
Section: Case Reports First Case: Patient #1mentioning
confidence: 99%
“…However, recently it was reported that a low cardiac MIBG uptake, but not a decreasing binding ratio on a dopamine transporter single photon emission computed tomography (DAT-SPECT), was helpful for early differential diagnosis of LBD from late-onset psychiatric disorders, even before parkinsonism or dementia appear. 13 In another study, it was reported that low cardiac MIBG uptake is detected before the diagnosis of probable DLB. 14 The high specificity of MIBG to detect LBD was repeatedly reported.…”
Section: Introductionmentioning
confidence: 97%